Role of Uric Acid as a Prognostic Factor in Acute Myocardial Infacrtion (Journal of Chittagong Medical College Teachers' Association, 2017)
Uric acid has been proven to be a negative prognostic indicator in patients with acute myocardial infarction and heart failure. So the aim of the present study is to evaluate the uric acid as a predictor of outcome after acute myocardial infarction. A total of 120 patients presenting with acute myocardial infarction were included in the study where case were the AMI with heart failure and arrhythmia and control were the only Ami patients. Patients were evaluated in relation with clinical features, risk factors, complications, heart failure with Killip Class and serum uric acid level. Sociodemographic profiles of the study populations were matched in case and control group. Regarding different biochemical variables of case and control where serum uric acid was found significantly higher among the case group than the control (p